ANALISIS PEMASARAN JERUK SIAM (CITRUS NOBILIS LOUR VAR) DI DESA KUOK KECAMATAN KUOK KABUPATEN KAMPAR - Arjuna Hasudungan; Ermi Tety; Eliza Eliza (Fakultas Pertanian, Universitas Riau, 2018)
The purpose of this research was to analyze the marketing of Siamese citrus in Kuok Village based on market performance. The location of research is determined purposively, that is the village which become the center of citrus production. Method of sampling the farmers was conducted by simple random sampling. Determination of sample marketing agency used snowball sampling method by following the marketing channel. Analysis of data included marketing cost analysis, marketing margin, marketing advantage, marketing efficiency, farmer's share and profit to cost ratio. The results showed that there are three marketing channels of citrus, namely the marketing channel I (farmers - collector traders – for Grade A, Grade B and Grade C), marketing channel II (farmers to retailers) and marketing channels III (farmers sell directly to end consumers). The analysis of market performance showed that the most efficient channels, based on the calculation of marketing costs, marketing margins, marketing advantages, marketing efficiency, farmer's share and profit-to-cost ratio is marketing channel II.